2004
DOI: 10.1080/00498250410001713131
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modelling of CYP2A enzymes: application to metabolism of the tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)

Abstract: 1. Tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is a lung carcinogen in a variety of animal models and a putative human lung carcinogen. Its tumorigenic potential is unmasked via cytochrome P450 (CYP)-mediated hydroxylation of the carbon atoms adjacent to the nitroso moiety (i.e. alpha-hydroxylation). Therefore, elucidation of enzyme-substrate interactions that facilitate alpha-hydroxylation is important to gain insight into the tumorigenic mechanism of NNK and to develop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This interaction may align substrates for oxidation and would provide an explanation for the low K m values observed for 5′-hydroxylation of (R)-and (S)-NNN (Table 2). Molecular models of NNK in P450 2A4 suggest that the loss of the π-π interaction with the pyridine ring of NNK due to Leu at position 209 explains its higher K m values (58). This phenomenon may also explain the kinetic parameters observed for NNN 5′-hydroxylation catalyzed by P450 2A4 (Table 2).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This interaction may align substrates for oxidation and would provide an explanation for the low K m values observed for 5′-hydroxylation of (R)-and (S)-NNN (Table 2). Molecular models of NNK in P450 2A4 suggest that the loss of the π-π interaction with the pyridine ring of NNK due to Leu at position 209 explains its higher K m values (58). This phenomenon may also explain the kinetic parameters observed for NNN 5′-hydroxylation catalyzed by P450 2A4 (Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…These residues may be contributing factors in (R)-NNN, (S)-NNN, and NPIP R-hydroxylation. In particular, molecular modeling studies with NNK docked in the active site of P450 2A5 suggested that Phe209 is positioned above the heme and could bind with substrates via π-stacking (58). This interaction may align substrates for oxidation and would provide an explanation for the low K m values observed for 5′-hydroxylation of (R)-and (S)-NNN (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of amino acid substitutions at these critical residues on NNK metabolic parameters deserves more attention. Recently, a structural model of P450 2A4 was constructed (85), and on the basis of this model, we have constructed models for a series of P450 2A enzymes (86). NNK docking experiments with these P450 models identified amino acid residues, including positions 117, 209, 365, and 481, which appear to be critical in the orientation of NNK in the active site.…”
Section: P450-catalyzed Metabolismmentioning
confidence: 99%
“…14,15,19,20,186 Furthermore, recent studies report that 6.7 (UCB) is a potent inhibitor of cytochrome P450 2A activities, 30,254 which is also known to contribute to the activation of some environmental carcinogens 36,255,256 . Bulmer et al 14 used the S9 fraction of rat liver homogenate and bacterial cultures to test the anti-mutagenic properties of 6.7 (UCB) and 6.8 (BV) and showed that both compounds efficiently inhibited revertant growth.…”
Section: The Competition Reactionsmentioning
confidence: 99%